Family physicians' perspectives on clinical guidelines, a survey from the Republic of Srpska, Bosnia and Herzegovina. (2nd July 2016) - Račić, Maja; Eremija, Svjetlana; Mašić, Srđan; Joksimović, Bojan N.; Stanetić, Kosana
Abstract: Background: Despite considerable efforts to promote and support clinical practice guidelines (CPGs) use, adherence has often been suboptimal universally. Objectives: The aim of this study was to assess to which extent family physicians (FPs) in Republic of Srpska (RS), Bosnia and Herzegovina (BiH) accept or reject the concept and practice of CPGs and evidence-based medicine (EBM). Methods: A cross-sectional survey was conducted among FPs from the RS, BiH in the period between January and March 2014. Recruitment of FPs was performed combining two different strategies, in-person recruitment at family medicine conferences and mailed invitations. The Questionnaire included19 questions from the existing Healthcare Monitor Questionnaire, divided into four thematic blocks and 11 self-designed questions. Results: Seventy-seven per cent of 131 interviewed physicians reported already using guidelines in the treatment of patients, while 22.9% of them are undecided or disagree. As the reason for rejecting guidelines, 13.0% of the physicians stated they did not support their content, 12.2% found that limited knowledge about guidelines prevented their application, and another 12.2% reported that the current guidelines were not practical enough. All groups would rather not use guidelines developed by a governmental institution. Conclusion: Most physicians in the RS, BiH accept and declare application of CPG. However, a substantial percentage remains sceptical, using CPGs only as an exception, or rejecting them due to their content or impracticability.